Analisis Pidato Kajian Retorika Aristoteles pada YouTube Video Perayaan Wisuda Virtual - Pramesthi, Jasmine Alya (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The state of COVID-19 that occurs in almost all parts of the world has made various activities carried out virtually from home in accordance with government policies. With all the activities done from home will cause several mental health problems. In order to provide support to the community, especially 2020 graduates who failed to celebrate graduation face-to-face, YouTube on June 7, 2020 broadcasts original content directly to carry out virtual graduation celebrations to congratulate, convey enthusiasm and inspiration to graduates with the title "Dear Class of 2020 ", one of the contents is entitled" BTS Commencement Speech | Dear Class of 2020 ”. By using a qualitative descriptive method, this study will try to explain how BTS rhetoric in delivering speeches in Dear Class of 2020, which is then analyzed using five rhetorical canons. The data analysis technique in this study is content analysis. Through the research results, the researcher found that all the speakers have five rhetorical canons delivered by Aristotle in their respective speeches. To require other research on rhetoric, the researcher suggests exploring other concepts outside the five rhetorical canon concepts in the study of Communication Studies.